Rapid generation cycling transforms pyrethrum (Chrysanthemum cinerariifolium) into an annualized perennial. Issue 2 (15th February 2021) - Anderson, Neil O.; Suranyi, Robert A.; Gullickson, Steven M.
Abstract: Pyrethrum [ Chrysanthemum cinerariifolium (Trevir.) Vis.] is an important "green pesticide" crop widely used for insect control on plants and for humans. Pyrethrum flowers have the highest Pyrethrin I/Pyrethrin II ratio (%Py) and are harvested at specific stages to maximize yield. Selection for correlative early seed germination and flowering in first year pyrethrum seedlings is challenging and has not been accomplished previously. The breeding objectives for this study were to sample a wide germplasm base to select for rapid generation cycling (RGC) traits of early and high germination in Weeks 1–4, earliness of visible bud date (VBD) and flowering, accelerated growth, high leaf unfolding rates per week, number of shoots, and %Py in the 1st–12th flowers. Seven seed lots were evaluated for germination rate and timing ( N  = 141, 120 seeds) in Year 1 for RGC traits. Seedling germination was recorded weekly with toothpicking to identify germination weeks with successive selection occurring at transplanting. Grand mean percentage germination was low (24.5%), whereas individual seed lots varied (18.4–38.9%). Seedling death was 0.0–6.8%. On average, it took 34–39 wk to reach VBD and an additional 3–4 wk to flower. Thus, flowering in <1 yr without vernalization is a new trait (annualized perennial) selected in this crop. Germination week was significantly correlated with VBD and flowering dates and is an important trait to use for selecting early‐flowering genotypes in plug trays. Pyrethrum breeding programs could select the earliest germinating seedlings (Weeks 1–4 after sowing) at transplanting to enhance the likelihood of selecting early‐flowering genotypes in the first year and provide an additional year of harvest to increase yield. Core Ideas: Novel breeding methodology is used to select in plug trays for early germination and early flowering. Novel transformation of pyrethrum was used to create an annualized perennial First‐ever analysis of pyrethrin content in the first 10–12 flowers of pyrethrum seedlings. Week of seed germination is correlated with number of weeks to visible bud and flowering dates.